Position specific morphological characteristics of elite water polo players - Lozovina, M.; Durovic, N.; Katic, R. (Collegium Antropologicum, 2009)
The aim of the study was to determine morphological characteristics of elite water polo players. In a sample of 121 water polo players, the structure of a set of 23 morphological space variables was determined by use of factor analysis, followed by determination of differences between all pairs of playing positions in the manifest morphological space by use of Post Hoc analysis. Factor structure indicated the presence of four basic superior latent dimensions responsible for directly measurable manifestations of morphological parameters: first component acting as a general mechanism of growth and development; second component being bipolar, at one pole almost exclusively determined by adipose tissue, and on the other pole by longitudinal skeletal growth; third component differentiating longitudinal skeletal growth accompanied by subcutaneous adipose tissue from muscle mass development and transverse skeletal growth; and fourth component mostly differentiating transverse skeletal development relative to longitudinal skeletal development. Oblimin transformation of the main components was employed to define the factor of circular dimensionality, factor of subcutaneous adipose tissue, factor of longitudinal skeleton dimensionality, and factor of transverse skeleton dimensionality. Results of obtained by the analysis of variance (ANOVA) and homogenization of playing positions in water polo for each individual variable upon Post Hoc analysis yielded significant differences both within and between groups in all anthropometric variables except for the variable of triceps skinfold. Statistically significant differences were recorded between two groups of playing positions, i.e. centers and backs versus goalkeepers, wingers and outside forwards. Significant differences were found between water polo players playing at center and back positions, characterized by higher values of all measures of longitudinal and transverse skeleton dimensionality in comparison with water polo players playing at other positions (goalkeepers, wingers and outside forwards). Significant differences were observed according to body mass and volume between water polo players playing at center position, characterized by considerably higher values of all measures in comparison with water polo players at other positions, and between centers and backs versus other positions according to body weight, chest circumference and forearm circumference. Considering subcutaneous adipose tissue, skinfold variable was significantly more pronounced in water polo players playing at center position than in those playing at other positions